Genome‐wide association study identifies the GLDC/IL33 locus associated with survival of osteosarcoma patients. Issue 8 (23rd December 2017) - Koster, Roelof; Panagiotou, Orestis A.; Wheeler, William A.; Karlins, Eric; Gastier‐Foster, Julie M.; Caminada de Toledo, Silvia Regina; Petrilli, Antonio S.; Flanagan, Adrienne M.; Tirabosco, Roberto; Andrulis, Irene L.; Wunder, Jay S.; Gokgoz, Nalan; et al.
Abstract : Survival rates for osteosarcoma, the most common primary bone cancer, have changed little over the past three decades and are particularly low for patients with metastatic disease. We conducted a multi‐institutional genome‐wide association study (GWAS) to identify germline genetic variants associated with overall survival in 632 patients with osteosarcoma, including 523 patients of European ancestry and 109 from Brazil. We conducted a time‐to‐event analysis and estimated hazard ratios (HR) and 95% confidence intervals (CI) using Cox proportional hazards models, with and without adjustment for metastatic disease. The results were combined across the European and Brazilian case sets using a random‐effects meta‐analysis. The strongest association after meta‐analysis was for rs3765555 at 9p24.1, which was inversely associated with overall survival (HR = 1.76; 95% CI 1.41–2.18, p = 4.84 × 10 −7 ). After imputation across this region, the combined analysis identified two SNPs that reached genome‐wide significance. The strongest single association was with rs55933544 (HR = 1.9; 95% CI 1.5–2.4; p = 1.3 × 10 −8 ), which localizes to the GLDC gene, adjacent to the IL33 gene and was consistent across both the European and Brazilian case sets. Using publicly available data, the risk allele was associated with lower expression of IL33 and low expression of IL33 was associated with poor survival in an independent set of patients with osteosarcoma. In conclusion, we have identified the GLDC / IL33 locus on chromosome 9p24.1 as associated with overall survival in patients with osteosarcoma. Further studies are needed to confirm this association and shed light on the biological underpinnings of this susceptibility locus. Abstract : What's new? To date, prognostic factors associated with survival in patients with osteosarcoma are scarce. Here, the authors conducted a multi‐institutional genome‐wide association study to explore whether germline genetics may contribute to overall survival in osteosarcoma patients. They identified a common single nucleotide polymorphism, rs55933544, located in the GLDC gene on chromosome 9, associated with poor survival. The rs55933544 risk allele was associated with lower expression of the nearby gene, IL33 . These findings, if replicated in additional populations, form the foundation for future studies of the molecular basis of the association of the GLDC/IL33 (rs55933544) variant with survival in osteosarcoma.